Examination of hookah usage and gambling status of university students* - Sen, Mehmet Ali; Pirincci, Edibe (Taylor & Francis Inc, 2024)
PurposeThis study examined hookah use by students, their gambling status, and the factors affecting it.Materials and MethodsThe research was descriptive and cross-sectional. A stratified random sampling method was used (n:1,724). A questionnaire and the South Oaks Gambling Screening Test (SOGS) were used to collect data. The data in the study were evaluated by number, percentage, average, t test, ANOVA, chi-square and regression tests in the SPSS 18.0 program.ResultsThe mean age of the students was 23.38 & PLUSMN; 4.98 years, and 57.3% were male. The average age for starting hookah smoking was 17.84 & PLUSMN; 3.61, and the smoking rate was 20.9%. The decrease in age, being a man, smoking, and smoking hookah in his immediate environment increases the student's hookah use (p < .05). In this study, gambling at least once in a lifetime was 22.8%, and possible pathological gambling was 1.0%. The SOGS score increases with age, low grades, alcohol use, low family communication, and dissatisfaction with life.ConclusionIn our study, the students' levels of substance use, especially hookah and gambling, were significant. Campaigns can be conducted to raise awareness among students about the dangers of hookah smoking and gambling addiction and to attract their attention to other areas.
Keywords: Hookah; gambling; college students; addiction